Sliding mode observer for biomass estimation in a biohydrogen production process - Nuñez, Sebastián (2012)
This work deals with the problem of estimation of biomass concentration and specific growth rate in a biohydrogen production process. A photo-fermentation process with the photosynthetic bacteria Rhodobacter capsulatus is considered. The reaction dynamics is represented with a Monod law while the hydrogen production rate is modeled with a Luedeking-Piret expression. A sliding mode observer is proposed and designed, which gives an estimate of both biomass concentration and specific growth rate from measurements of the produced hydrogen volume. The proposed observer is completely robust against the growth kinetic model, and it presents a first-order reduced dynamics. Numerical simulation results are presented for a batch biohydrogen production process.